Effects of Reynolds and Prandtl Numbers on Heat Transfer Around a Circular Cylinder by the Simplified Thermal Lattice Boltzmann Model (Communications in Computational Physics, 2018)
In this paper, the fluid flow and heat transfer around a circular cylinder arestudied under various conditions (Reynolds number 10 ≤ Re ≤ 200; Prandtl number,0.1 ≤ Pr ≤ 2). To solve the governing equations, we use the simplified thermal latticeBoltzmann model based on double-distribution function approach, and present a correspondingboundary treatment for both velocity and temperature fields. Extensivenumerical results have been obtained to the flow and heat transfer behaviors. Thevortices and temperature evolution processes indicate that the flow and temperaturefields change synchronously, and the vortex shedding plays a determinant role in theheat transfer. Furthermore, the effects of Reynolds and Prandtl number on the flowand isothermal patterns and local and averaged Nusselt numbers are discussed in detail.Our simulations show that the local and averaged Nusselt numbers increase withthe Reynolds and Prandtl numbers, irrespective of the flow regime. However, the minimumvalue of the local Nusselt number can shift from the rear point at the back of thecylinder with higher Prandtl number even in the steady flow regime, and the distributionof the local Nusselt number is almost monotonous from front stagnation point torear stagnation point with lower Prandtl number in the unsteady flow regime.